2004
DOI: 10.4040/jkan.2004.34.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model on Mother-infant Attachment during the Early Postpartum Period

Abstract: It is necessary that the nurses provide postpartum women with an intervention using social support for improving maternal identity and alleviating maternal role strain. It can be helpful to improve maternal sensitivity and in the end it will facilitate the mother-infant attachment during postpartum period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…Over the past few decades, numerous studies of maternal attachment have focused on identifying the major influential factors of MIA (Britton et al. 2001, Ohta 2001, Shin et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous studies of maternal attachment have focused on identifying the major influential factors of MIA (Britton et al. 2001, Ohta 2001, Shin et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, numerous studies of maternal attachment have focused on identifying influencing factors of mother–infant attachment (Mercer & Ferketich 1990, Muller 1996, Britton et al. 2001, Ohta 2001, Damato 2004, Shin et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2004). Factors such as postpartum depression, prenatal attachment, the mother's age, perceived support, delivery methods, and maternal competence affected mother–infant attachment (Mercer & Ferketich 1990, Muller 1996, Ohta 2001, Damato 2004, Shin et al. 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a positive and nurturing environment beginning in the very first year of life is essential for children to build secure attachment bonds with his or her parents or primary caregivers [6][7][8][9]. Research from the National Academy of Sciences has shown that children with well-developed social and cognitive skills are more likely to be successful and require less resources and social support from intervention services.…”
Section: Short Communicationmentioning
confidence: 99%